Preparation method of special throwing high-temperature adhesive for connecting carbon / carbon material and invar steel

By preparing high-temperature adhesives containing zirconium tungstate, copper pyrophosphate and other materials, the problem of differences in thermal expansion coefficients and mismatch between carbon/carbon composite materials and Yinsteel is solved, and stable connection and high-strength adhesive are achieved at high temperatures Connection effect.

CN119241268APending Publication Date: 2025-01-03CIVIL AVIATION UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411276467.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The difference in thermal expansion coefficient between carbon/carbon composite materials and Yin steel leads to failure of connections, and the physical and chemical properties do not match, making it difficult to achieve stable connections, especially in high temperature environments.

Method used

Using materials such as zirconium tungstate, copper pyrophosphate, boron carbide, silicon powder and aluminum phosphate, low expansion regulator and aluminum phosphate glue base liquid are prepared through specific mixing and grinding processes to form high-temperature adhesives to ensure adhesives Maintain stable mechanical properties and chemical stability at high temperatures.

Benefits of technology

It provides bonding strength above 10MPa, reduces the thermal expansion coefficient, ensures the reliability and stability of the connection parts, reduces thermal stress, avoids crack propagation, and significantly improves the long-term performance and service life of the connection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241268A_ABST
    Figure CN119241268A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation process of a high-temperature adhesive, which is specially designed for bonding a carbon / carbon material and invar steel and has excellent high-temperature bonding performance. The process comprises the following steps: firstly, preparing a matrix aluminum phosphate gel base solution of the adhesive, then preparing reaction powder containing silicon, boron carbide and a low-expansion regulator, and finally, uniformly mixing the aluminum phosphate gel base solution and the reaction powder to obtain the high-temperature adhesive with high bonding strength and low thermal expansion coefficient. And strict requirements on material connection performance in an extreme environment are met. The preparation method has the advantages that the preparation process is easy to operate, green and free of pollution, renewable materials are used as raw materials, and the requirements for environmental protection and sustainable development are met; the bonding strength of 10 MPa or above is provided at the room temperature, after heat treatment, the bonding strength of 2-5 MPa can also be provided within the temperature range of 100-600 DEG C, and the connection stability under the extreme conditions of high temperature, mechanical load and the like is ensured; the thermal expansion coefficient of the adhesive is low, and the thermal expansion coefficient of a bonded carbon / carbon and invar bonding piece is reduced to be below 2.5 * 10 <-6 > K <-1 >, so that the thermal stress can be reduced, and the reliability of a connecting part is improved; the adhesive layer is in close contact with an interface, the high-compatibility interface steady state between the adhesive layer and a base material is maintained, it is ensured that the bonding strength is still stable under wide temperature changes, and no remarkable performance degradation phenomenon exists.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive material preparation, and in particular relates to a method for preparing a special high-temperature adhesive for connecting carbon / carbon material with Invar. Background Art

[0002] Carbon / carbon composite materials show unique material advantages with their low density, excellent thermal conductivity, high strength and toughness, excellent thermal shock resistance and corrosion resistance, especially stability in high temperature environments. Invar materials play an indispensable role in aerospace and mechanical manufacturing, and their extremely low thermal expansion coefficient is crucial to improving equipment stability. Effectively connecting carbon / carbon composite materials with Invar not only achieves the dual goals of structural lightweighting and functional optimization, but also significantly improves the performance and reliability of the overall system. This technology has shown broad application potential in many fields such as high-energy physics, military equipment and civil engineering.

[0003] At present, the connection between the two is mainly used for three-dimensional coordinate measuring machines, which are one of the commonly used measuring instruments. They can quickly and conveniently measure the size parameters of parts that cannot be measured by some ordinary measuring instruments. The measuring axes of existing three-dimensional coordinate measuring axes are mostly made of aluminum alloy materials. Due to the large thermal expansion coefficient of aluminum alloy materials, the measuring reference of the measuring axis, the grating scale, will be damaged and the accuracy will change after a few years of use. Therefore, how to overcome the problem of damaged accuracy of the measuring axis has become a problem that needs to be solved urgently.

[0004] The combined structure of Invar and carbon / carbon composite material increases the strength of the shaft and reduces its weight without changing its size, reducing the damage to the measurement reference caused by thermal expansion and the deformation of the measurement shaft caused by inertial force. However, the significant difference in the thermal expansion coefficient between carbon / carbon composite material and Invar is one of the core challenges facing connection technology. This difference leads to significant stress concentration at the interface during temperature changes. With the accumulation of thermal cycles, it is easy to cause crack propagation and connection failure, seriously threatening the long-term performance and service life of the product. In addition, the mismatch between the physical and chemical properties of the two, such as differences in thermal conductivity and chemical stability, further increases the difficulty of achieving a stable connection.

[0005] In view of the above problems, the development of a low thermal expansion adhesive that can overcome the difference in thermal expansion between materials and has excellent heat resistance, anti-aging properties and good bonding strength has become a key technical breakthrough in the field of carbon / carbon composite and Invar connection. This adhesive must have stable mechanical properties and chemical stability under extreme environments to cope with complex and changing working conditions and ensure the long-term reliability and precision of the connection parts. Therefore, in-depth research on the formulation design, preparation process and interface action mechanism of adhesives has great scientific significance and engineering value for promoting the development of carbon / carbon composite and Invar connection technology and improving the comprehensive performance of products in related fields. Summary of the invention

[0006] In order to solve the above problems, the object of the present invention is to provide a method for preparing a special high-temperature adhesive for connecting carbon / carbon materials and Invar.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a special high-temperature adhesive for connecting carbon / carbon material and Invar steel, which specifically comprises the following steps:

[0008] (1) mixing zirconium tungstate powder and copper pyrophosphate powder in a mass ratio of 0-1:0-1, placing the mixture in a ball mill, wherein the mass ratio of zirconium oxide grinding balls to mixed powder is 8-12:0.5-1.5, and mixing the mixture at a speed of 300-400 r / min for 24-36 hours to obtain a low expansion regulator;

[0009] (2) Preliminarily mixing boron carbide, silicon powder and the low expansion regulator prepared in step (1) in a mortar in a mass ratio of 1-2:3-4:3-12, and then mixing them uniformly in a vortex mixer at an oscillation speed of 600-3200 rpm / min to obtain a reaction powder containing silicon-boron carbide-low expansion regulator;

[0010] (3) diluting 85% concentrated phosphoric acid with water to a concentration of 55-65% dilute phosphoric acid;

[0011] (4) Stirring the dilute phosphoric acid prepared in step (3) in a constant temperature water bath at 80-85°C, setting the stirring speed to 250-300 r / min, and slowly adding aluminum hydroxide to the dilute phosphoric acid solution at a solid-liquid mass ratio of 0.5-1.5:2-3. After the aluminum hydroxide is completely dissolved, mechanically stir the mixed solution at a speed of 400-600 r / min for 2-3 hours, and after stirring is complete, a milky aluminum phosphate gel-based liquid is obtained;

[0012] (5) The aluminum phosphate gel base liquid prepared in step (4) is transferred to a mortar containing a reaction powder containing silicon-boron carbide-low expansion regulator, mixed, and ground for 20-40 minutes to obtain a high-temperature adhesive for connecting carbon / carbon materials and Invar steel.

[0013] Preferably, in step (1), the particle sizes of the zirconium tungstate and copper pyrophosphate are both 6-8 μm. The reagents used in the reaction can be purchased from various chemical reagent manufacturers.

[0014] Preferably, in step (2), the particle size of the boron carbide powder is 6-10 μm, and the particle size of the elemental silicon powder is 0.5-5 μm, and the purity of both is higher than 99%.

[0015] Preferably, in steps (3) and (4), the concentrated phosphoric acid and aluminum hydroxide are both analytically pure, wherein the purity of aluminum hydroxide is 99% and the particle size is 10-25 μm. The reagents used in the reaction can be purchased from various chemical reagent manufacturers. The water in step (3) can be any water source and has no effect on the process.

[0016] The preparation method of the special high-temperature adhesive for connecting carbon / carbon material and Invar provided by the present invention has the following beneficial effects:

[0017] 1. The preparation process is simple, green and pollution-free, and uses renewable materials as raw materials, which meets the requirements of environmental protection and sustainable development.

[0018] 2. It provides a bonding strength of more than 10MPa at room temperature. After heat treatment, it can also provide a bonding strength of 2-5MPa in the temperature range of 100-600℃, ensuring the stability of the connection under extreme conditions such as high temperature and mechanical load;

[0019] 3. The thermal expansion coefficient of the adhesive is reduced to 2.5×10 -6 K -1 The following reduces thermal stress and improves the reliability of the connection parts;

[0020] 4. The adhesive layer achieves close contact with the interface, maintains a highly compatible interface steady state with the substrate, and ensures that the bonding strength remains stable under a wide range of temperature changes without significant performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The bending shear strength of the bonded parts of carbon / carbon material and Invar bonded by the special high temperature adhesive for connecting carbon / carbon material and Invar prepared in Example 1 and the commonly used aluminum phosphate adhesive (blank sample) tested at room temperature after being treated at different temperatures;

[0022] Figure 2 The test force-displacement curve of the bonded piece of carbon / carbon material and Invar bonded by the special high-temperature adhesive for connecting carbon / carbon material and Invar prepared in Example 1 (after being treated at 100° C.) under the room temperature bending shear test;

[0023] Figure 3The XRD patterns of the high temperature adhesive for connecting carbon / carbon material and Invar prepared in Example 1 after being treated at room temperature, 50°C, 80°C, 100°C, and 200°C;

[0024] Figure 4 The XRD patterns of the high temperature adhesive for connecting the carbon / carbon material and the Invar prepared in Example 1 after being treated at 300° C., 400° C., 500° C., and 600° C.;

[0025] Figure 5 FTIR spectra of the high temperature adhesive for connecting carbon / carbon material and Invar prepared in Example 1 after being treated under different temperature conditions;

[0026] Figure 6 This is a scanning electron microscope photo of the bonding area of ​​the carbon / carbon material and the Invar bonded by the special high temperature adhesive for connecting the carbon / carbon material and the Invar prepared in Example 1 after being treated at 600°C.

[0027] Figure 7 This is the thermal expansion curve of the carbon / carbon material and Invar bonded by the special high temperature adhesive for connecting the carbon / carbon material and Invar prepared in Example 1 after heat treatment at 100°C. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments.

[0029] Example 1

[0030] The present embodiment provides a method for preparing a special high-temperature adhesive for connecting carbon / carbon material and Invar, comprising the following steps performed in sequence:

[0031] (1) zirconium tungstate and copper pyrophosphate powders were mixed in a mass ratio of 0:1, placed in a ball mill, wherein the mass ratio of zirconium oxide grinding balls to mixed powders was 10:1, and fully mixed at a speed of 350 r / min for 24 hours to obtain a low expansion regulator;

[0032] (2) placing boron carbide, silicon powder and the low expansion regulator prepared in step (1) in a mortar in a mass ratio of 3:7:12, and then placing them in a vortex mixer and mixing them uniformly at an oscillation speed of 2800 rpm / min to obtain a reaction powder containing silicon-boron carbide-low expansion regulator;

[0033] (3) diluting 85% concentrated phosphoric acid with water to a concentration of 60% dilute phosphoric acid;

[0034] (4) Stir the dilute phosphoric acid prepared in step (3) in a constant temperature water bath at 82°C, set the stirring speed to 270 r / min, and slowly add aluminum hydroxide to the dilute phosphoric acid solution at a solid-liquid mass ratio of 1:2.5. After the aluminum hydroxide is completely dissolved, mechanically stir the mixed solution at a speed of 500 r / min for 3 hours, and after stirring is complete, obtain a milky white aluminum phosphate gel-based liquid;

[0035] (5) The aluminum phosphate gel-based liquid prepared in step (4) is transferred to a mortar containing a reaction powder containing silicon-boron carbide-low expansion regulator, mixed, and ground for 30 minutes to obtain a high-temperature adhesive specifically for connecting carbon / carbon materials and Invar steel.

[0036] Example 2

[0037] The present embodiment provides a method for preparing a high-temperature adhesive for connecting carbon / carbon material and Invar, comprising the following steps in sequence:

[0038] (1) zirconium tungstate and copper pyrophosphate powders were mixed in a mass ratio of 1:0, placed in a ball mill, wherein the mass ratio of zirconium oxide grinding balls to mixed powders was 12:1.5, and fully mixed at a speed of 400 r / min for 24 hours to obtain a low expansion regulator;

[0039] (2) placing boron carbide, silicon powder and the low expansion regulator prepared in step (1) in a mortar in a mass ratio of 1:2:6 for preliminary mixing, and then placing in a vortex mixer at an oscillation speed of 3200 rpm / min for uniform mixing to obtain a reaction powder containing silicon-boron carbide-low expansion regulator;

[0040] (3) diluting 85% concentrated phosphoric acid with water to a concentration of 65% dilute phosphoric acid;

[0041] (4) Stir the dilute phosphoric acid prepared in step (3) in a constant temperature water bath at 85°C, set the stirring speed to 270 r / min, and slowly add aluminum hydroxide to the dilute phosphoric acid solution at a solid-liquid mass ratio of 1:2. After the aluminum hydroxide is completely dissolved, mechanically stir the mixed solution at a speed of 600 r / min for 3 hours, and after stirring is complete, obtain a milky white aluminum phosphate gel-based liquid;

[0042] (5) The aluminum phosphate adhesive base liquid prepared in step (4) is transferred to a mortar containing a reaction powder containing silicon-boron carbide-low expansion regulator, mixed, and ground for 40 minutes to obtain a high-temperature adhesive specifically for connecting carbon / carbon materials and Invar steel.

[0043] Example 3

[0044] The present embodiment provides a method for preparing a high-temperature adhesive for connecting carbon / carbon material and Invar, comprising the following steps in sequence:

[0045] (1) zirconium tungstate and copper pyrophosphate powders were mixed in a mass ratio of 1:1, placed in a ball mill, wherein the mass ratio of zirconium oxide grinding balls to mixed powders was 8:0.5, and fully mixed at a speed of 300 r / min for 24 hours to obtain a low expansion regulator;

[0046] (2) placing boron carbide, silicon powder and the low expansion regulator prepared in step (1) in a mortar in a mass ratio of 1:3:3 for preliminary mixing, and then placing in a vortex mixer and mixing at an oscillation speed of 600 rpm / min to obtain a reaction powder containing silicon-boron carbide-low expansion regulator;

[0047] (3) diluting 85% concentrated phosphoric acid with water to a concentration of 55% dilute phosphoric acid;

[0048] (4) Stir the dilute phosphoric acid prepared in step (3) in a constant temperature water bath at 80°C, set the stirring speed to 250 r / min, and slowly add aluminum hydroxide to the dilute phosphoric acid solution at a solid-liquid mass ratio of 1:4. After the aluminum hydroxide is completely dissolved, mechanically stir the mixed solution at a speed of 400 r / min for 2 hours, and after the stirring is complete, obtain a milky white aluminum phosphate gel-based liquid;

[0049] (5) The aluminum phosphate gel base liquid prepared in step (4) is transferred to a mortar containing a reaction powder containing silicon-boron carbide-low expansion regulator, mixed, and ground for 20 minutes to obtain a high-temperature adhesive specifically for connecting carbon / carbon materials and Invar steel.

[0050] The high-temperature adhesive provided by the present invention is specifically used for connecting carbon / carbon materials with Invar, and its matrix is ​​an amorphous aluminum phosphate colloid obtained by reacting phosphoric acid with aluminum hydroxide. Under high temperature conditions, the aluminum phosphate colloid generates high-temperature resistant compounds such as aluminum phosphate with different crystal structures. These compounds wrap high-temperature resistant oxide particles to form a strong chemical bonding force, so that the adhesive has excellent high-temperature resistance and ensures that the entire adhesive system can still maintain high bonding strength and excellent mechanical properties at high temperatures. Boron carbide and silicon can not only improve the viscosity of the adhesive, but also enhance the mechanical properties of the adhesive matrix through the particle strengthening mechanism. In addition, the oxidation of silicon powder and boron carbide under high temperature conditions can also compensate the volume of the adhesive matrix to maintain the integrity of the adhesive matrix. When the temperature reaches a certain value, the oxidized boron oxide and silicon oxide will generate borosilicate glass, further improving the strength and temperature resistance of the adhesive matrix. Thermal expansion regulators are a type of negative thermal expansion material. Their addition effectively reduces the thermal expansion coefficient of the adhesive, making the thermal expansion coefficient of the adhesive more closely matched to the bonded parts, thereby preventing the generation and expansion of cracks in the adhesive layer during thermal cycling.

[0051] In order to verify the use effect of the high temperature adhesive provided in the above embodiment, the inventors conducted the following experiments:

[0052] 1) Lay the polished, cleaned and dried carbon / carbon material (10×10×30 mm) and Invar (10×10×30 mm) on a smooth and flawless glass plate with the bonding surface facing upwards;

[0053] 2) Preparation of blank aluminum phosphate adhesive: Boron carbide and silicon powder were placed in a mortar at a mass ratio of 3:7 for preliminary mixing, and then placed in a vortex mixer at an oscillation speed of 2000rpm / min to mix evenly to obtain a reaction powder containing silicon-boron carbide; concentrated phosphoric acid with a concentration of 85% was diluted with water to a dilute phosphoric acid with a concentration of 60%; the prepared dilute phosphoric acid was stirred in a constant temperature water bath at 85°C, the stirring speed was set to 250r / min, and aluminum hydroxide was slowly added to the dilute phosphoric acid solution at a solid-liquid mass ratio of 39:49. After the aluminum hydroxide was completely dissolved, the mixed solution was mechanically stirred at a speed of 500r / min for 2h, and a milky aluminum phosphate glue base liquid was obtained after the stirring was complete; the prepared aluminum phosphate glue base liquid was transferred to a mortar containing the reaction powder containing silicon-boron carbide, mixed, and ground for 30min to obtain a blank aluminum phosphate adhesive.

[0054] 3) The high temperature adhesive prepared in Example 1 and the blank aluminum phosphate-based adhesive were brushed onto each bonding surface, with a bonding area of ​​10×10 mm, and then the thickness of the high temperature adhesive on each bonding surface was controlled to 200 μm using an applicator;

[0055] 4) The carbon / carbon material coated with adhesive is bonded to the Invar steel with the bonding surfaces facing each other to form a bonded part, and then the bonded part of the carbon / carbon material and the Invar steel is dried and cured at room temperature. After curing, the bonded part is placed in a forced air drying oven and a muffle furnace and calcined at different temperatures (50°C, 80°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C) for 1 hour;

[0056] 5) Room temperature bending shear test: The bending shear strength of the adhesive prepared in Example 1 and the blank aluminum phosphate-based adhesive after being treated at different temperatures was tested using a CSS-44001 universal testing machine. The bonding strength of the high-temperature adhesive specially used for connecting carbon / carbon materials to Invar was evaluated by comparative experiments. The bonding strength of the adhesive after being treated at different temperatures was as follows: Figure 1 At the same time, the test force-displacement curve of the bonded parts (after 100°C treatment) bonded by the special high-temperature adhesive for connecting carbon / carbon material and Invar steel at room temperature after bending shear test is recorded, as shown in FIG. Figure 2 As shown;

[0057] Depend on Figure 1 It can be seen that the high-temperature adhesive prepared in Example 1 can provide a bonding strength of not less than 11MPa at room temperature, and can also provide a bonding strength of not less than 3MPa for the connection between carbon / carbon materials and Invar within the treatment temperature range of 100-200°C; the bonding strength within the treatment temperature range of 200-600°C is maintained at around 3MPa. In contrast, the bonding strength provided by the commonly used blank aluminum phosphate-based adhesive is very low. After being treated at a temperature of 200-600°C, the bonding strength provided is no more than 1MPa. It can be seen that the high-temperature adhesive specially used for connecting carbon / carbon materials and Invar prepared in the present invention has excellent bonding properties, which can greatly improve the application effect of the bonding process.

[0058] Depend on Figure 2 It can be seen that the test force-displacement curve of the adhesive bonded by the adhesive prepared in Example 1 drops off sharply after reaching the highest point, indicating that the adhesive is brittle fracture and has a large stiffness, which is consistent with the ceramic characteristics.

[0059] 6) Adhesive composition analysis: The composition of the adhesive prepared in Example 1 after being treated at different temperatures was analyzed using an XRD tester (D / Max 2500v / PC, Rigaku). The XRD spectra of the adhesive after being treated at different temperatures are as follows: Figure 3 and Figure 4 As shown;

[0060] Depend on Figure 3 and Figure 4It can be seen that under room temperature conditions, the adhesive is composed of an amorphous phase, unreacted Al(OH)3, Si, B4C and Cu2P2O7. After treatment at 200°C, the amorphous phase decomposes to form AlPO4 with different crystal structures. Al(OH)3 is converted into Al2O3 by dehydration, but since the peak of Al2O3 is not shown in the XRD spectrum, it is speculated that the generated Al2O3 is amorphous. As the temperature increases, the aluminum phosphate undergoes a crystal transformation. The XRD peak intensity of B4C and Si decreases, indicating that they also begin to be oxidized. As the temperature continues to rise, the decomposition and dehydration of phosphates and Al(OH)3, the conversion of aluminum phosphate, and the oxidation of B4C appear in the adhesive in turn. These phase changes that occur with increasing temperature will significantly affect the bonding effect of the adhesive.

[0061] 7) Infrared spectrum analysis of adhesive: Infrared spectroscopy (Nicolet, Waliham, USA) was used to analyze the molecular bonding changes of the adhesive prepared in Example 1 after being treated at different temperatures. The infrared spectra of the adhesive treated at different temperatures are as follows: Figure 5 As shown;

[0062] Depend on Figure 5 It can be seen that compared with the RT spectrum, it is found that at 1100cm -1 and 430cm -1 v(-PO) and 720cm -1 The absorption peak intensity at v(-AlO) increases significantly after heat treatment at 200℃-600℃, which corresponds to the decomposition of amorphous phosphate and Al(OH)3. The BO peak is more obvious at high temperature, indicating the oxidation of B4C.

[0063] 8) Bonding surface morphology analysis: The bonded parts treated at 600°C were made into SEM test specimens, and the microscopic morphology of the cross section of the bonded parts was tested using a scanning electron microscope analyzer (Nanosem430, FEI). Figure 6 As shown;

[0064] Depend on Figure 6 It can be seen that the thickness of the adhesive layer is maintained at about 200 μm after treatment at 600 °C. This uniform thickness distribution and proper laying of the adhesive play a key role in effectively dispersing the local stress on the interface. In addition, the adhesive forms a close contact with the surface of the Invar and carbon / carbon materials. The adhesive almost completely fills the microscopic pores and cracks at the interface, reducing the presence of air bubbles and voids.

[0065] 9) Thermal expansion performance analysis: The thermal expansion coefficient curve of carbon / carbon material and Invar connector after heat treatment at 100℃ was tested using German NETZSCH DIL 402C thermomechanical analysis equipment. Figure 7 shown.

[0066] from Figure 7 It can be clearly seen from the data that the thermal expansion coefficient of the prepared carbon / carbon material and the Invar bond increases with the increase of temperature. When the temperature rises from room temperature to 70°C, the thermal expansion coefficient of the material increases rapidly and the volume expands sharply; after 70°C, the expansion rate tends to be flat, and the volume remains basically unchanged. The thermal expansion coefficient can reach up to 2.45×10 -6 k -1 .

Claims

1. A method for preparing a special high temperature adhesive for connecting carbon / carbon material and Invar, characterized in that: The preparation method comprises the following steps performed in sequence: (1) Mix zirconium tungstate and copper pyrophosphate powders in a mass ratio of 0-1:0-1 and place them in a ball mill, wherein the mass ratio of zirconium oxide grinding balls to mixed powder is 8-12: 0.5-1.5, fully mix at a speed of 300-400r / min for 24-36h to obtain a low expansion regulator; (2) Preliminarily mixing boron carbide, silicon powder and the low expansion regulator prepared in step (1) in a mortar in a mass ratio of 1-2:3-4:3-12, and then mixing them uniformly in a vortex mixer at an oscillation speed of 600-3200 rpm / min to obtain a reaction powder containing silicon-boron carbide-low expansion regulator; (3) diluting 85% concentrated phosphoric acid with water to a concentration of 55-65% dilute phosphoric acid; (4) Stir the dilute phosphoric acid prepared in step (3) in a constant temperature water bath at 80-85°C, set the stirring speed to 250-300 r / min, and slowly add aluminum hydroxide to the dilute phosphoric acid solution at a solid-liquid mass ratio of 0.5-1.5:2-3. After the aluminum hydroxide is completely dissolved, mechanically stir the mixed solution at a speed of 400-600 r / min for 2-3 hours, and after stirring is complete, obtain a milky white aluminum phosphate gel-based liquid; (5) According to the solid-liquid mass ratio of 8-17:23-27, the aluminum phosphate gel-based liquid prepared in step (4) is transferred to a mortar containing the reaction powder containing silicon-boron carbide-low expansion regulator prepared in step (2), mixed, and ground for 20-40 minutes to obtain a high-temperature adhesive specially used for connecting carbon / carbon materials and Invar steel.

2. The method for preparing the special high temperature adhesive for connecting carbon / carbon material and Invar according to claim 1, characterized in that: In step (1), the particle sizes of zirconium tungstate and copper pyrophosphate are both 6-8 μm. The reagents used in the reaction can be purchased from various chemical reagent manufacturers.

3. The method for preparing the special high temperature adhesive for connecting carbon / carbon material and Invar according to claim 1, characterized in that: In step (2), the particle size of the boron carbide powder is 6-10 μm, and the particle size of the elemental silicon powder is 0.5-5 μm, and the purity of both is higher than 99%.

4. The method for preparing the special high temperature adhesive for connecting carbon / carbon material and Invar according to claim 1, characterized in that: In steps (3) and (4), the concentrated phosphoric acid and aluminum hydroxide are both analytically pure, wherein the purity of aluminum hydroxide is 99% and the particle size is 10-25 μm. The reagents used in the reaction can be purchased from various chemical reagent manufacturers. The water in step (3) can be any water source and has no effect on the process.